Second-Stage Music Teachers' Perceptions of Their Professional Development. (April 2013) - Eros, John
In recent years, professional development has become a topic of an increasing amount of research. However, studies are often general in nature or focused on beginning teachers specifically. Recently, researchers have begun to explore professional development over the course of a teacher's entire career. The purpose of this study was to investigate the professional development needs of a particular population of experienced teachers: those known as second-stage teachers, commonly defined as teachers who have experience of 4 to 10 years and have passed the "survival years." Research questions were as follows: (a) How do second-stage music teachers describe their professional development experiences? and (b) How do second-stage music teachers perceive their professional development needs? Findings are organized into the following themes: forms of professional development, professional development needs at different times, obstacles to professional development, and concerns about a lack of professional development.